Coronavirus pandemic and its effect on African religiosity - Mbosowo Bassey Udok; Clement Usen Eton; Ekpenyong Nyong Akpanika (Center for Humanities and Innovation Studies, 2020)
Coronavirus is the latest pandemic that is challenging all spheres of the human economy globally. The popular